2017
DOI: 10.1007/s10694-017-0675-x
|View full text |Cite
|
Sign up to set email alerts
|

Fire Performance of Phase Change Material Enhanced Plasterboard

Abstract: Abstract. Sustainable construction materials are increasingly being used to reduce the carbon footprint of modern buildings. These materials have the potential to change the fire dynamics of compartments by altering the compartment energy balance however there is little quantitative understanding of how these materials behave in the event of a real fire. The changes in fire dynamics may be due to increased fuel load in a compartment, reduced time to failure or promotion of flame spread. The objective of this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Oxidation of paraffin wax from these boards was observed at 210 C to 250 C 32 and this agrees well with the exothermic oxidation reaction observed at 233 C of PCM microcapsules heated at 5 C/min. 33 Evaporation of paraffin wax was observed from 227 C to 347 C and the shell melted during 280 C to 450 C as reported in Reference 29.…”
Section: Pcm-plasterboardsupporting
confidence: 87%
“…Oxidation of paraffin wax from these boards was observed at 210 C to 250 C 32 and this agrees well with the exothermic oxidation reaction observed at 233 C of PCM microcapsules heated at 5 C/min. 33 Evaporation of paraffin wax was observed from 227 C to 347 C and the shell melted during 280 C to 450 C as reported in Reference 29.…”
Section: Pcm-plasterboardsupporting
confidence: 87%
“…The obtained results from the test indicated that there is no ignition in the reference PB, producing negligible THR of 0.7 MJ/m 2 with mass loss of 18.9%. This is attributed to release of water molecules in the crystal lattice of PB in the form of water vapor at high temperatures due to the dehydration reactions, contributing to improve the fire resistance of wall as a result of the reduction in wall temperature 53,66 . As shown in Figure 10A and Table 4, all samples containing ISOP burned with two peaks of heat release rate.…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, the flammability of organic PCM is considered the prime significant threat for use in buildings. The flammability of PCMs is emerging in the literature 11,53,54 . In case of a fire, significant amounts of smoke, flame, and toxic gases 55,56 can be produced as a result of the burning of PCMs, which can be transferred simply through the building, causing deaths, injures, and property losses 57,58 …”
Section: Introductionmentioning
confidence: 99%
“…In the daytime, PCMs melt by absorbing energy from the surrounding environment and then re-solidify at night, releasing the stored energy. This process reduces the need for cooling in the daytime and heating at night [56,57].…”
Section: Water Wall With Phase Change Materials (Pcms)mentioning
confidence: 99%